2002
DOI: 10.1016/s0960-9822(01)00660-1
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Type Iα Phosphatidylinositol 4-Phosphate 5-Kinase in Neurite Remodeling

Abstract: Rapid neurite remodeling is fundamental to nervous system development and plasticity and is regulated by Rho family GTPases that signal f-actin reorganization in response to various receptor ligands. Neuronal N1E-115 cells show dramatic neurite retraction and cell rounding in response to serum factors such as lysophosphatidic acid (LPA), sphingosine-1 phosphate (S1P), and thrombin, due to activation of the RhoA-Rho kinase pathway. Type I phosphatidylinositol 4-phosphate 5-kinases (PIPkinase), which regulate ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 24 publications
4
47
1
Order By: Relevance
“…We have shown recently that the RhoA effector, Rho-kinase, which mediates signals from RhoA to the actin cytoskeleton (36), is involved in RhoA-dependent regulation of PIP5K activity (37). In agreement, in intact CV1 cells (16) and platelets (38), PIP 2 formation is reduced by the Rhokinase inhibitor, Y27632, and in N1E-115 neuroblastoma cells, PIP5K functions as downstream effector of RhoA-and Rhokinase in neurite remodeling (39,40). Rho GTPases were also found to physically associate with type I PIP5K.…”
mentioning
confidence: 68%
“…We have shown recently that the RhoA effector, Rho-kinase, which mediates signals from RhoA to the actin cytoskeleton (36), is involved in RhoA-dependent regulation of PIP5K activity (37). In agreement, in intact CV1 cells (16) and platelets (38), PIP 2 formation is reduced by the Rhokinase inhibitor, Y27632, and in N1E-115 neuroblastoma cells, PIP5K functions as downstream effector of RhoA-and Rhokinase in neurite remodeling (39,40). Rho GTPases were also found to physically associate with type I PIP5K.…”
mentioning
confidence: 68%
“…In terms of their cellular functions, PIP5K1s are also involved in the regulation of actin reorganization and focal adhesion dynamics, which are critical in cell migration (51) and neurite outgrowth (52,53). Among all PIP5K1s, PIP5K1C is mainly expressed in brain and required for cardiovascular and neuronal development.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a previous report indicated that Sema3A-mediated neurite retraction requires instead the activity of another isoform of PIPK, © 2 0 0 6 C o p y r i g h t E u r e k a h / L a n d e s B i o s c i e n c e D o N o t D i s t r i b u t e called PIPK-Iα. 111 Although not localized to focal contacts, PIPK-Iα activity was shown to induce vinculin dissociation from the adhesive complexes and release substrate adhesion. 111 Therefore, the regulation of PIP2 levels at the cell surface seems to be an important mechanism to account for semaphorin-mediated control of cell-substrate adhesion and actin remodelling.…”
Section: Integrins and The Actin Cytoskeleton Are Major Targets Of Plmentioning
confidence: 99%
“…111 Although not localized to focal contacts, PIPK-Iα activity was shown to induce vinculin dissociation from the adhesive complexes and release substrate adhesion. 111 Therefore, the regulation of PIP2 levels at the cell surface seems to be an important mechanism to account for semaphorin-mediated control of cell-substrate adhesion and actin remodelling.…”
Section: Integrins and The Actin Cytoskeleton Are Major Targets Of Plmentioning
confidence: 99%